2003
DOI: 10.1021/ac0342323
|View full text |Cite
|
Sign up to set email alerts
|

Ratiometric Optical PEBBLE Nanosensors for Real-Time Magnesium Ion Concentrations Inside Viable Cells

Abstract: This paper presents the development and characterization of a highly selective magnesium fluorescent optical nanosensor, made possible by PEBBLE (probe encapsulated by biologically localized embedding) technology. A ratiometric sensor has been developed by co-immobilizing a dye that is sensitive to and highly selective for magnesium, with a reference dye in a matrix. The sensors are prepared via a microemulsion polymerization process, which entraps the sensing components inside a polymer matrix. The resultant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
124
0
2

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 189 publications
(128 citation statements)
references
References 35 publications
2
124
0
2
Order By: Relevance
“…Previous work on both polyacrylamide-based and sol-gel based PEBBLE sensors also demonstrated that the matrix, as expected, prevented macromolecules such as proteins (e.g. bovine serum albumin) from diffusing through [27][28][29]. The matrix protected entrapped dyes from the intracellular environment, thus diminishing interference with the fluorescent properties of the dyes [25].…”
Section: Prevention Of Enzymatic Reduction Of Mb By the Matrixsupporting
confidence: 59%
“…Previous work on both polyacrylamide-based and sol-gel based PEBBLE sensors also demonstrated that the matrix, as expected, prevented macromolecules such as proteins (e.g. bovine serum albumin) from diffusing through [27][28][29]. The matrix protected entrapped dyes from the intracellular environment, thus diminishing interference with the fluorescent properties of the dyes [25].…”
Section: Prevention Of Enzymatic Reduction Of Mb By the Matrixsupporting
confidence: 59%
“…These materials show promise for a wide array of applications, including substrates for neuronal cell growth (Mattson et al 2000;Hu et al 2004;Lovat et al 2005), scaffolding for tissue and bone growth (Usui et al 2008), supports for liposaccharides to mimic cell membranes (Chen et al 2004), ion channel blockers (Park et al 2003a(Park et al , 2003b, tumor imaging (Zavaleta et al 2008), and drug delivery systems (Bianco and Prato 2003;Bianco et al 2005aBianco et al , 2005bBianco et al , 2005cBagonluri 2008a, 2008b). In addition to their medical applications, carbon nanotubes are expected to advance electronics, within energy storage devices, thermal insulators, conducive fillers, and molecular electronic devices (Baughman 2000;Gao et al 2000;Katz and Willner 2004;Bianco et al 2005bBianco et al , 2005cFortina et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Optode nanoparticles intended to provide an alternative method for imaging ions intracellularly have been in development for years. 14 We have built upon this previous research to create nanosensors specific for intracellular sodium imaging that will hopefully provide a means to understand how sodium signaling affects cellular function and alterations in signaling which lead to certain diseases.…”
Section: Discussionmentioning
confidence: 99%